PEMBELAJARAN BERBASIS SOFT SKILL UNTUK MAHASISWA ENTREPRENEURSHIP DENGAN MODEL KELOMPOK USAHA BERSAMA - Aprilina Susandini; Faidal Faidal (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2019)
Learning innovation is learning by using new ideas, methods and models toachieve learning goals. The Entreprenurship Study Program improves students' soft skillswith a joint business group model. Where this business group is used as a place ofpractice for students to apply the learning process in the classroom. The aim is toincrease student creativity in carrying out their business ideas. The implementation ofKUB model learning uses a qualitative approach, where data is obtained by means ofinterviews and observations. KUB will be managed by students, while lecturers superviseand provide direction.